2011
DOI: 10.1021/ja206610u
|View full text |Cite
|
Sign up to set email alerts
|

An Easily Accessible Isoindigo-Based Polymer for High-Performance Polymer Solar Cells

Abstract: A new, low-band-gap alternating copolymer consisting of terthiophene and isoindigo has been designed and synthesized. Solar cells based on this polymer and PC(71)BM show a power conversion efficiency of 6.3%, which is a record for polymer solar cells based on a polymer with an optical band gap below 1.5 eV. This work demonstrates the great potential of isoindigo moieties as electron-deficient units for building donor-acceptor-type polymers for high-performance polymer solar cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
313
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 366 publications
(323 citation statements)
references
References 42 publications
9
313
1
Order By: Relevance
“…, which more than compensated for a decrease in V oc to 0.70 V. 9,21 Evidently, despite the similar chemical structures a very different photovoltaic performance is obtained, which necessitates an in-depth investigation of relevant structure-property relationships of these oligothiophene-isoindigo polymers.…”
Section: à2mentioning
confidence: 99%
“…, which more than compensated for a decrease in V oc to 0.70 V. 9,21 Evidently, despite the similar chemical structures a very different photovoltaic performance is obtained, which necessitates an in-depth investigation of relevant structure-property relationships of these oligothiophene-isoindigo polymers.…”
Section: à2mentioning
confidence: 99%
“…59,74,75 It has been hypothesized that such a morphology can not only facilitate exciton dissociation and but can also provide an easier route to percolation of the charge-carriers to their respective electrodes, 59 which can improve the J SC , without significantly affecting the V OC . 5,74 Moreover, due to the simplicity of the process compared to thermal or solvent annealing, 42,72 the incorporation of solvent additives is emerging as a popular route for improving the organic solar cell device performance.…”
Section: Tuning the Morphology: Effect Of Additivesmentioning
confidence: 99%
“…6.3%). 5 Amb et al reported BHJ devices based on dithienogermole-based polymers P-Si and P-Ge as donors and PC 71 BM as an acceptor. 17 TEM images of the devices revealed a dramatic difference in the extent of polymer-fullerene phase segregation and grain boundaries for devices processed with and without additives, with large PC 71 BM domains of dimensions 100-350 nm (lateral) and 45-65 nm (vertical) clearly seen for devices processed in the absence of additives (Fig.…”
Section: Tuning the Morphology: Effect Of Additivesmentioning
confidence: 99%
“…1). Extending these structures with dimers of thiophenes moves absorption into the infrared, but does not improve efficiency at first (Wang et al 2010b) but with improved processing comes to better than 6% (Wang et al 2011).…”
Section: Designer Polymersmentioning
confidence: 99%